More Than Resveratrol: New Insights into Stilbene-Based Compounds - Paulina Pecyna; Joanna Wargula; Marek Murias; Malgorzata Kucinska (Biomolecules, 2020)
The concept of a scaffold concerns many aspects at different steps on the drug development path. In medicinal chemistry, the choice of relevant “drug-likeness” scaffold is a starting point for the design of the structure dedicated to specific molecular targets. For many years, the chemical uniqueness of the stilbene structure has inspired scientists from different fields such as chemistry, biology, pharmacy, and medicine. In this review, we present the outstanding potential of the stilbene-based derivatives. Naturally occurring stilbenes, together with powerful synthetic chemistry possibilities, may offer an excellent approach for discovering new structures and identifying their therapeutic targets. With the development of scientific tools, sophisticated equipment, and a better understanding of the disease pathogenesis at the molecular level, the stilbene scaffold has moved innovation in science. This paper mainly focuses on the stilbene-based compounds beyond resveratrol, which are particularly attractive due to their biological activity. Given the “fresh outlook” about different stilbene-based compounds starting from stilbenoids with particular regard to isorhapontigenin and methoxy- and hydroxyl- analogues, the update about the combretastatins, and the very often overlooked and underestimated benzanilide analogues, we present a new story about this remarkable structure.